Exploring the Intersection of Board Gender Diversity, Culture, and ESG Reporting: A Bibliometric Study - Sundarasen, Sheela; Ali, Ahnaf Alsmady; Zyznarska-Dworczak, Beata; Mahmood, Nor Asiah (Journal of Ecohumanism, 2024)
This study provides a bibliometric and content analysis on selected scholarly work in the realms of board gender diversity and ESG reporting. The study analyzed 383 articles published between 1998 and 2023 from the Scopus database. Using both Vosviewer and Biblioshiny R-package, numerical and visualization techniques are used to examine the literature. The results show an upsurge in publications of articles within this domain, indicating their relevance and importance in the current business landscape. The review concludes that board gender diversity is integral to ESG outcomes and sustainable corporate practices, but culture and institutional characteristics need to be considered when generalizing the findings. Thus, context-specific strategies could play a pivotal role to further enhance the relationship between board gender diversity and ESG outcomes. This study has significant implications for policymaking, business strategies, societal decisions, and academic research, which could contribute to quality sustainability reporting and business sustainability.